Prevalence of Alcohol Use Disorders and Their Association with Sociodemographic Determinants and Depression/Anxiety Disorders in a Representative Sample of the Greek General Population. (10th February 2020) - Bellos, Stefanos; Petrikis, Petros; Malliori, Meni; Mavreas, Venetsanos; Skapinakis, Petros
Abstract : Background . Country-level epidemiological data about alcohol-related problems is useful for planning prevention and treatment services. Heavy Alcohol Consumption (HAC) and Alcohol Use Disorder (AUD) are two syndromes of alcohol-related problems that have been recognized worldwide. Study of the epidemiological determinants of HAC and AUD in different sociocultural contexts could inform hypotheses about the etiology or the consequences of alcohol-related problems. Objectives . We assessed the prevalence and associations of HAC and AUD with sociodemographic variables adjusting for common mental disorders in a representative sample of the general population of Greece (N = 4894 participants). The period of data collection just preceded the emergence of the financial crisis in Greece. Results . The majority of the population did not report HAC, AUD or abstinence from alcohol. HAC was reported by 12.7% (95% CI: 11.8–13.6) of the population while 3.1% (95% CI: 2.7–3.6) met criteria for AUD. Younger age, divorce, lower educational level, living in an urban area, physical health problems, and smoking were associated with a higher prevalence of both conditions. Presence of severe financial difficulties and never married family status were associated with a higher prevalence of HAC but not AUD. HAC was associated with nonspecific psychiatric morbidity while AUD was associated with more specific psychiatric disorders. Conclusion/Importance . Both alcohol-related problems are frequent in the general population and have common and distinct determinants. The comparison between the findings of our study and those of similar studies during or after the period of financial austerity in Greece, would offer the opportunity to assess the possible effects of changes in the economical context in the determinants of alcohol-related problems.